Development of an air quality station using low-cost sensors - Roncaglio, Mateus Maruzka; Camargo, Edson Tavares de; Martins, Leila Droprinchinski; Oyamada, Marcio Seiji (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2023)
Air pollution is one of the most important health problems causing various diseases. According to the World Health Organization (WHO), it is estimated that more than 7 million deaths are due to air pollution. For this reason, air quality monitoring is an important indicator for guiding public policy. However, government stations are widely scattered and their high cost makes it unprofitable to invest in higher resolution. Low-cost air quality monitoring sensors can overcome this problem, but also bring new challenges. This paper presents the development of a low-cost air quality monitoring device. The low-cost station collects the following measurements: carbon monoxide (CO), nitrogen dioxide (NO2), sulfur dioxide (SO2), ozone (O3), and particulate matter. The collected data is corrected using a machine learning model and sent to the Internet in real time via the LoRaWAN protocol. Mean square error (MSE), root mean square error (RMSE), mean absolute error (MAE), linearity coefficient (R2), and Pearson r were used to compare model performance. Our results show that linear models such as the Alphasense equation and linear model regression cannot accurately describe the sensor response to the reference gas sensor, whereas the RF model performs better in each metric. The performance of the RF model demonstrates the potential to improve air quality monitoring and the decision-making process.